The Role of Cultivation Techniques on the Attack of Etiella zinckenella Pests in Chickpea Crops - Patty, John Alfred (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Development in the agricultural sector is dominant in the Maluku Province region, because the majority of the population works in agriculture. One of the agricultural locations is Telaga Kodok Hamlet which has a fairly large planting area, so people tend to cultivate vegetable crops such as chickpea plants (Phaseolus vulgaris). In the cultivation of bean plants, both quality and quantity are affected by pest attacks, so it is necessary to pay attention to proper control techniques. One of the pests that attack chickpea pods is pod borer (Etiella zinckenella). This study aims to determine the intensity of damage to chickpea pods and to determine the crop cultivation system to suppress the development of Etiella zinckenella pests. This research was conducted in farmers' plantation areas in Telaga Kodok Hamlet, Hitu Lama Village, Leihitu District, Central Maluku Regency in March 2024. The research methods used included surveys and direct observations in bean planting areas to observe Etiella zinckenella pest attacks and assess the intensity of damage. The results of this study showed that the type of pest that attacked bean plants in the farmers' area in Telaga Kodok Hamlet was pod borer (Etiella zinckenella) with an average attack intensity of 48.13% and was classified as moderate. Bean cultivation techniques such as tillage, fertilization, use of varieties, sanitation, pest control have not been implemented properly. In controlling pests, farmers rely more on the use of synthetic pesticides with concentrations and mixing methods that are not in accordance with the rules of use.